2008
DOI: 10.1016/j.atmosenv.2007.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variation in vehicle-derived metal pollution identified by magnetic and elemental analysis of roadside tree leaves

Abstract: Exposure to metal-rich particulate pollution is associated with adverse health outcomes. In particular, lead has recently been shown to be toxic in young children even at low levels previously considered 'safe'. Lead poisoning from vehicle pollution has been addressed internationally by removal of leaded petrol but toxic blood lead levels in children continue to be reported in urban areas, the source suggested to be resuspended roadside soil, enriched in lead due to previous leaded fuel usage. Here, we use pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
148
0
12

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(167 citation statements)
references
References 42 publications
7
148
0
12
Order By: Relevance
“…However, several studies have also identified Fe having origins from traffic sources (Adamo et al, 2008;Amato et al, 2009;Ault et al, 2012;Catinon et al, 2013;Maher et al, 2008), and somehow the comparison between samples from FFP and FFS sites also describes this trend (a higher Fe concentration is recorded at FFS site). However, the traffic-related effect on Fe concentration is dwarfed by the overwhelming factory influence, which increases the average Fe concentration by a factor of three.…”
Section: Discussionmentioning
confidence: 88%
“…However, several studies have also identified Fe having origins from traffic sources (Adamo et al, 2008;Amato et al, 2009;Ault et al, 2012;Catinon et al, 2013;Maher et al, 2008), and somehow the comparison between samples from FFP and FFS sites also describes this trend (a higher Fe concentration is recorded at FFS site). However, the traffic-related effect on Fe concentration is dwarfed by the overwhelming factory influence, which increases the average Fe concentration by a factor of three.…”
Section: Discussionmentioning
confidence: 88%
“…Secondly, deciduous trees are more efficient in intercepting dust particles from the pollutant stream than coniferous trees. Magnetic particles are found in the leaf and needle structures of various tree species (Schädlich et al 1995;Matzka and Maher 1999;Hanesch et al 2003;Urbat et al 2004;Gautam et al 2005;Lehndorff et al 2006;Maher et al 2008;Sagnotti et al 2009). However, these are few inclusions of single particles without any significant influence on soil magnetic susceptibility.…”
Section: Magnetic Susceptibility Of Soilsmentioning
confidence: 99%
“…The concentrations of Pb in model organisms reached very high values, exceeding several times the permitted limits (Table 2). Especially lead poisoning from vehicle pollution has been addressed internationally by removal of leaded petrol (Maher et al 2008). Metals such as Fe, Cu, Zn are essential components of many alloys, pipe, wire and tyres in motor vehicles and are released into the roadside environment as the result of mechanical abrasion and normal wear and tear (Huber et al 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The presence of iron in dust particles around petrol stations are predominantly caused by car bodies' corrosion and has no connection to the combustion of petrol. Chromium and copper are also used for the surface treatment of materials and subject to corrosion (Maher et al 2008). Yıldırım and Tokalıoğlu (2016) who evaluated the heavy metal content in street dust have found a significant positive correlation between the pairs: Ni-Co, Zn-Cu and Cd-Pb.…”
mentioning
confidence: 99%